2018
DOI: 10.1073/pnas.1810664115
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for anthrax toxin receptor 1 recognition by Seneca Valley Virus

Abstract: SignificanceAnthrax toxin receptor 1 (ANTXR1), also known as Tumor Endothelial Marker 8, is overexpressed on the surface of tumor cells in over 60% of human cancers. A serious drawback for developing specific ligands for targeted therapy against ANTXR1 is the cross-reactivity with ANTXR2. Recently, ANTXR1 was identified as the high-affinity cellular receptor for Seneca Valley Virus (SVV). SVV has shown promising results as an oncolytic agent in clinical trials, and this discovery offers a powerful biomarker fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Moreover, ANTXR1 knockout mutations protected SVV-susceptible cells in vitro and in mice models, conclusively showing that the cellular receptor for SVV is ANTXR1 [65]. This was further corroborated by the elucidation of the structural basis for the interaction of SVV and ANTXR1 by cryo-electron microscopy [114]. Seneca Valley Virus (SVV) in the form of wild-type strain SVV-001 has been evaluated for selective infection and lysis of cancers including retinoblastoma [67], medulloblastoma [66], glioma [68] and small-cell lung cancer, reaching as far as Phase II clinical trials [115].…”
Section: Seneca Valley Virusmentioning
confidence: 89%
“…Moreover, ANTXR1 knockout mutations protected SVV-susceptible cells in vitro and in mice models, conclusively showing that the cellular receptor for SVV is ANTXR1 [65]. This was further corroborated by the elucidation of the structural basis for the interaction of SVV and ANTXR1 by cryo-electron microscopy [114]. Seneca Valley Virus (SVV) in the form of wild-type strain SVV-001 has been evaluated for selective infection and lysis of cancers including retinoblastoma [67], medulloblastoma [66], glioma [68] and small-cell lung cancer, reaching as far as Phase II clinical trials [115].…”
Section: Seneca Valley Virusmentioning
confidence: 89%
“…Its homologous receptor, ANTXR2, is expressed on both healthy and tumor cells and acts as the main cellular receptor for the protective antigen of anthrax toxin secreted by the gram-positive bacterium Bacillus anthracis [ 28 ]. The cryo-EM structure of SVV-ANTXR1 showed that despite a large degree of structural and sequence conservation between the two receptors, the sequence along the SVV binding footprint shows divergence, thereby limiting SVV attachment only to ANTXR1 [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…238 Our group identified the surface exposed loops on SVV-001 capsid exterior, BC loop, loop II of VP1, the "puff" loop of VP2, and the "knob" loop of VP3 which form the binding site for the extracellular domain of ANTXR1 ( Figure 4G). 239 Furthermore, we showed that SVV binding site on ANTXR1 is non-conserved in its paralogous receptor, ANTXR2, which is expressed in normal cells, thereby providing a structural basis for tumor specificity of SVV. 240 SVV empty capsid binds ANTXR1, suggesting it may have potential as a vaccine or as virus-like particles for the development of tumor-targeted delivery of drugs.…”
Section: Seneca Valley Virusmentioning
confidence: 94%